African hosts and their guests : cultural dynamics of tourism - Beek, W. E. A. van; Schmidt, A. M. (Annette M.), 1967- (James Currey, 2012)
For Western tourists Africa embodies the Romantic ideal of 'nature', where they go to have adventures in the game parks and encounters with colourful cultures and picturesque people. In the long list from slavery to colonialism and from liberation to globalisation, international tourism is one of the latest global dynamics engaging the people on the continent, but the agency of the receiving partners is much larger than it was in the colonies. The differences stand out in what constitutes the heart of this book, the encounter in the field between 'hosts' and 'guests'.